A Large-Scale Outbreak of Echovirus 30 in Gansu Province of China in 2015 and Its Phylodynamic Characterization - Chen, Jianhua; Han, Zhenzhi; Wu, Haizhuo; Xu, Wenbo; Yu, Deshan; Zhang, Yong (Frontiers in Microbiology, 2020)
Background: Echovirus 30 (E-30) has been investigated and reported worldwide and is closely associated with several infectious diseases, including encephalitis; myocarditis; and hand, foot, and mouth disease. Although many E-30 outbreaks associated with encephalitis have been reported around the world, it was not reported in northwest China until 2015. Methods: The clinical samples, including the feces, serum, throat swabs, and cerebrospinal fluid, were collected for this study and were analyzed for diagnosis. E-30 was isolated and processed according to the standard procedures. The epidemiological and phylogenetic analysis were performed to indicate the characteristics of E-30 outbreaks and phylodynamics of E-30 in China. Results: The E-30 outbreaks affected nine towns of Gansu province in 2015, starting at a school of Nancha town and spreading to other towns within one month. The epidemiological features showed that children aged 6-15 years were more susceptible to E-30 infection. The genotype B and C co-circulated in the world, whereas the latter dominated the circulation of E-30 in China. The genome sequences of this outbreak present 99.3% - 100% similarity among these strains, indicating a genetic-linked aggregate outbreak of E-30 in this study. Two larger genetic diversity expansions and three small fluctuations of E-30 were observed from 1987 to 2016 in China, which revealed the oscillating patterns of E-30 in China. In addition, the coastal provinces of China, such as Zhejiang, Fujian and Shandong, were initially infected, followed by other parts of the country. The E-30 strains isolated from mainland of China may have originated from Taiwan of China in the last century. Conclusion: The highly similarity E-30 genomes in this outbreak showed an aggregate outbreak of E-30, with 9 towns affected. Our results suggested that although the genetic diversity of E-30 oscillates, the dominant lineages of E-30 in China has complex genetic transmission. The coastal provinces played an important role in E-30 spread, which implied further development of effective countermeasures. This study provides a further insight into the E-30 outbreak and transmission, and illustrates the importance of valuable surveillance in the future.